Cardiac patient undergoing cancer treatment: Implications for nursing care (Research, Society and Development, 2021)
People who need cancer treatment can develop cardiovascular diseases due to the cancer treatment used, such as chemotherapy and radiotherapy. These types of treatments can cause cardiotoxicity, which is generated by the accumulation of certain chemicals in the heart. This study sought to describe the particularities of cancer treatment in cardiac patients, in addition to describing nursing care for patients with heart disease who are undergoing cancer treatment using chemotherapy and radiotherapy. The research is a bibliographic review with a descriptive and qualitative approach. It is necessary to develop and implement guidelines for the use of chemotherapy and radiotherapy, as only with a standardized and systematized clinical practice, it will be possible to guarantee safety in the treatment of cancer patients with heart disease. The main nursing care in cancer patients with heart disease are self-care education interventions, monitoring vital signs, decubitus changes according to the need previously diagnosed by the nurse, patient positioning, medication management, treatment programs such as: serotherapy, colon preparation, infusion tube care, medical, nursing records and exam references, control of fluid intake, guarantee of airway permeability, daily dressing and pain control. It is hoped that this work will contribute to improving the systematization of care for cardiac cancer patients, as well as contributing to future publications on this topic.